INVESTIGATION OF THE STRUCTURE OF THE ENDOMETRIUM AS A MANDATORY COMPONENT PREGRAVIDARY PREPARATION IN WOMEN WITH VARIOUS FORMS OF HYPERANDROGENYА - Ліхачов В. К.; Семенюк Л. М.; Тарановська О. О. (World of Medicine and Biology, 2014)
Work is devoted to providing the body's hormonal characteristics of women in different forms of hyperandrogenism, and morpho -functional features of endometrial receptors, dominated by androgens. Established that reproductive disorders in women in this group due to polymorphism histomorphological changes in endometrial secretory phase of the menstrual cycle due to violation expression of receptors for estrogen and progesterone in the stroma and glandular endometrial cells. High efficiency of office hysteroscopy and endometrial biopsy samples plucked for visual evaluation and histomorphological study the structural features of the endometrium at the stage of prehravidary preparation for women with various forms of hyperandrogenism.
Keywords: hyperandrogenia; the endometrium; the expression of sex steroids; morphological indices